Social Support with Post-Traumatic Growth among Trauma Survivors: A Systematic Review - Muhammad Ferly Aditya; Mustikasari Mustikasari; Yudi Ariesta Chandra; Yossie Susanti Eka Puteri (Indonesian Journal of Global Health Research, 2025)
Natural and non-natural disasters can cause long-term psychological impacts on affected individuals, including the emergence of post-traumatic stress disorder. However, some victims actually experience positive changes known as post-traumatic growth (PTG), which is psychological growth that occurs after facing a traumatic event. PTG does not form automatically, but is influenced by various factors, one of which is social support. Effective social support can strengthen resilience, provide a sense of security, and facilitate the reinterpretation of the trauma experienced. Objective to identify and synthesize scientific evidence regarding the relationship between social support and PTG in disaster victims.Method: This study used a systematic review design, with article searches conducted through three main databases: PubMed, CINAHL, and Scopus. The keywords used were: “post-traumatic growth” OR “PTG” AND “social support” AND “disaster” OR “natural disaster” OR “earthquake” OR “flood” OR “tsunami”. Inclusion criteria included original research articles published in English between 2015–2025 and explicitly discussing the relationship between social support and PTG in disaster victim populations. Data were extracted manually using a table that included the author, purpose, design, sample, location, instrument, and results of the study. Data analysis was conducted descriptively qualitatively with a thematic analysis approach. A total of 10 articles that met the inclusion criteria were successfully identified and analyzed. The results of the study showed that social support consistently plays a role in encouraging the occurrence of PTG through various mechanisms: as a direct predictor, a mediator between psychological factors (such as resilience and survivor guilt), and as a moderator of the relationship between psychopathological symptoms and PTG. Six main themes were found in the thematic analysis: the direct role of social support, psychological mediation, moderating function on depression and anxiety, strengthening resilience, diversity of support sources, and vicarious PTG experiences. PTG does not solely depend on individual characteristics, but is also influenced by the extent to which they are connected to a supportive social environment. Therefore, nursing practice needs to integrate aspects of social support in disaster victim care, either through family, community, or professional service approaches.